2023
DOI: 10.1039/d3ra02069j
|View full text |Cite
|
Sign up to set email alerts
|

Full-dimensional neural network potential energy surface and dynamics of the CH2OO + H2O reaction

Abstract: A first dynamical study based on an accurate full-dimensional neural network PES for the CH2OO + H2O reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 55 publications
(62 reference statements)
1
9
0
Order By: Relevance
“…[29][30][31]34 Recently, we reported the first full-dimensional potential energy surface (PES) of the CH 2 OO + H 2 O reaction, covering the reactants to HMHP, which extends to various end products, including the hydroxymethoxy radical (HOCH 2 O, HMO) + OH, formic acid (HCOOH) + H 2 O, and formaldehyde (CH 2 O) + H 2 O 2 . 35 The rate coefficients calculated with transition state theory agree well with the experimental results. The quasiclassical Roaming, an unconventional yet intriguing mechanism, promises to yield unexpected products with final distributions remarkably distinct from those generated by the traditional MEP.…”
Section: ■ Introductionsupporting
confidence: 72%
See 4 more Smart Citations
“…[29][30][31]34 Recently, we reported the first full-dimensional potential energy surface (PES) of the CH 2 OO + H 2 O reaction, covering the reactants to HMHP, which extends to various end products, including the hydroxymethoxy radical (HOCH 2 O, HMO) + OH, formic acid (HCOOH) + H 2 O, and formaldehyde (CH 2 O) + H 2 O 2 . 35 The rate coefficients calculated with transition state theory agree well with the experimental results. The quasiclassical Roaming, an unconventional yet intriguing mechanism, promises to yield unexpected products with final distributions remarkably distinct from those generated by the traditional MEP.…”
Section: ■ Introductionsupporting
confidence: 72%
“…The full-dimensional PES used in this study was a modified PES for the CH 2 OO + H 2 O reaction we reported recently. 35 Figure 1 shows the schematic diagrams of the PES, illustrating the configurations and energies of stationary points. Figure 1a corresponds to the collision of CH 2 OO and H 2 O, which gives rise to the formation of HMHP.…”
Section: ■ Methodsmentioning
confidence: 99%
See 3 more Smart Citations